Study on RFID Implementation on Safety Vest for Real-time Human Safety Prevention in Construction Site - Shahhin, Shafeena; Kasim, Narimah (Research in Management of Technology and Business, 2025)
Safety remains a significant issue in the construction industry, particularly in Malaysia, where high accident rates persist. Implementing RFID technology in safety vests offers a proactive approach to real-time risk monitoring, potentially transforming safety protocols on construction sites. This study aims to investigate the implementation of RFID on safety vests for real-time worker safety prevention in the construction site. Therefore, this study aims to investigate the potential, challenges, and strategies to promote RFID implementation on safety vests for real-time human safety on construction sites. A qualitative research methodology was used, combining primary data from semi-structured interviews with individuals in Malaysia, such as a technical executive, a founder, business development manager, a government agency representative, and site safety supervisor. Respondents are selected based on their extensive expertise and comprehensive experience in the utilization of RFID systems. Secondary data is sourced from books, academic journals, conference proceedings, and other credible publications. Content analysis was applied to examine the potential and challenges of RFID technology in safety vests for real-time safety monitoring. The study found that RFID could enhance incident response by alerting workers when they approach hazardous areas. However, resistance from workers in adapting to new technologies, such as RFID, emerged as a significant challenge. To address this, the study identified education and training programs as the most effective strategy for facilitating RFID adoption. In conclusion, RFID-enabled safety vests hold great potential to improve safety on construction sites, and overcoming worker resistance through comprehensive education and training is essential for successful implementation.